Satisfaction level and masticatory capacity in edentulous patients with conventional dentures and implant-retained overdentures - Pocztaruk, Rafael de Liz (2016)
The difficulty of totally edentulous individual in performing the basic oral functions in a satisfactory and pleasant way directs the investigations for improvement of the rehabilitation techniques. This study aimed to perform an intra-patient analysis of the satisfaction level and masticatory capacity during the phases of the rehabilitation treatment with osseointegrated implants. Twelve edentulous patients (mean age: 61 years) participated. Satisfaction level and masticatory capacity were analyzed based on specific questionnaires for edentulous patients and by a verbal rating scale from 0 to 10, at three moments: with the old dentures, with conventional new ones after they had been received two osseointegrated implants in the mandible (after 60 days of use). After 5 months of the first surgical phase, gold cap ball attachments were adapted and the last evaluation was performed with the upper denture and the lower overdenture, after 30 days of use. The Friedman test was applied. The rehabilitation with implants produced a significant improvement in the satisfaction level (95.83%) and the masticatory capacity (94.07%). The new full dentures produced a better satisfaction and masticatory capacity than the old dentures. Besides, lower overdenture supported by two osseointegrated implants and a new upper conventional denture produced a higher scores than the conventional new dentures.